Investment management & the Philippine stock market - Aragon, Bienvenido M.; Cayanan, Arthur S.; Clemente, Lilia Calderon; Echanis, Erlinda; Guidote, Corazon; Ilano, Alberto; Jacinto, Ricardo N.; Mariano, Roberto; Quiason, Enrique; Rodriguez, Rafael A.; Sazon, Teodoro D.; Teh, Shirley; et al. (Diliman, Quezon City : Development Center for Finance, 1995)
Investing in stock market has been and always will be a risky business. This statement is true not just in the Philippines but everywhere where stock market exist.
CHAPTER 1. Introduction -- 2. The basics of Capital markets -- 3. Stock Market Rules and Conventions -- 4. Principles of Securities Regulations -- 5. The Macroeconomic Environment -- 6. Company Analysis -- 7. The Valuation of Common stocks -- 8. Technical Analysis -- 9. Quantitative Techniques for Philippine Stock Market Analysis -- 10. Portfolio Management -- 11. Investment Management and a case study: Managing the First Philippine Fund -- 12. Equity Derivatives: An Introduction.
Includes index.
Keywords: PHILIPPINE STOCK MARKET EXCHANGE; CAPITAL MARKET -- PHILIPPINES; INVESTMENT -- PHILIPPINES